2013
DOI: 10.11622/smedj.2013197
|View full text |Cite
|
Sign up to set email alerts
|

Advances in rehabilitation medicine

Abstract: Rehabilitation medicine is the medical specialty that integrates rehabilitation as its core therapeutic modality in disability management. More than a billion people worldwide are disabled, and the World Health Organization has developed the International Classification of Functioning, Disability and Health as a framework through which disability is addressed. Herein, we explore paradigm shifts in neurorehabilitation, with a focus on restoration, and provide overviews on developments in neuropharmacology, reha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 134 publications
(325 reference statements)
0
16
0
Order By: Relevance
“…It does so through producing high-intensity, active, repetitive and task-oriented movements, utilising the principles of motor learning. (8) A 2011 Cochrane article on the use of VR-based therapy in stroke recovery, which reviewed 19 randomised controlled trials (with a total of 565 poststroke participants), concluded that there was some evidence that VR-based therapy was more effective than conventional interventions and achieved better arm function.…”
Section: Discussionmentioning
confidence: 99%
“…It does so through producing high-intensity, active, repetitive and task-oriented movements, utilising the principles of motor learning. (8) A 2011 Cochrane article on the use of VR-based therapy in stroke recovery, which reviewed 19 randomised controlled trials (with a total of 565 poststroke participants), concluded that there was some evidence that VR-based therapy was more effective than conventional interventions and achieved better arm function.…”
Section: Discussionmentioning
confidence: 99%
“…According to the review by Ng et al, 2013 [18], the frailty requires a new approach based on the following reasons. Firstly, frailty is interconnected but may occur irrespective of any comorbidity or inability [19, 20].…”
mentioning
confidence: 99%
“…Secondly, frailty is associated with a greater risk of hospital readmission, admission to a care home, a worse outcome following surgery, post-operative complications and a greater risk of falling, dementia, general morbidity and mortality. Thirdly, it is potentially reversible as a result of specific intervention such as rehabilitation and exercise [18]. …”
mentioning
confidence: 99%
“…14 The introduction of BoNT-A has had a significant impact on the treatment of focal spasticity in the upper limbs, and it is widely viewed as a welltolerated and efficacious treatment option (when used appropriately, based on the relevant country-specific guidance and applicable summary of product characteristics) in conjunction with physical therapy programmes. 25,[34][35][36][37][38] Preliminary studies suggest that it is best delivered early, when spastic paresis first sets in, in order to minimise the development of secondary complications, such as contractures. 39 It is important to note that patients must also exercise and receive physical and occupational therapy, as long-term disuse can induce muscle atrophy.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…However, many patients contend with insufficient outpatient rehabilitation and monitoring in the long term ( Table 5). 8 Although physical therapy (stretching, positioning and splints) remains the mainstay of the management of spastic paresis, 36 the goals of physical therapy are often not well defined, leading to patients feeling unmotivated and disheartened, which may mean they decide to discontinue their rehabilitation. Variations in treatment frequency or reliance on multiple therapists can also affect the patient's confidence in the therapy and their perception of its usefulness.…”
Section: Patient Factorsmentioning
confidence: 99%